Numbered Head Together Model Assisted by Concrete Media on Students' Critical Thinking Ability in Mathematics Learning - Putri, Ni Komang Ratih Purnama; Wiarta, I Wayan (Thinking Skills and Creativity Journal, 2024)
Learning mathematics is one of the subjects that students consider difficult. This is because students do not understand the concepts given. Students have low critical thinking skills, because in learning teachers do not use appropriate learning models and learning media that suit student characteristics. Teachers only use conventional learning models. Based on this, a learning model is needed that can improve critical thinking skills. This research aims to analyze the significant influence of the NHT type cooperative model assisted by concrete media on students' critical thinking abilities in fifth grade elementary school mathematics learning. This research is a quasi-experimental research with a non-equivalent control group design. The population of this study was all class V totaling 217 students. The research sample was determined using a cluster random sampling technique which obtained class V of as many as 38 students as experimental class and class V as many as 30 students as the control class. The data collection method in this research is the test method, with the type of test used being the description test. Data obtained from the post-test results were analyzed using descriptive statistical techniques and inferential statistical analysis using the polled variance t-test. Based on data analysis, the results showed that the NHT type cooperative model assisted by concrete media had a significant effect on students' critical thinking abilities in fifth grade elementary school mathematics learning.